Current-Mode Quadrature Qscillator and Universal Filter Using ZC-CCFTAs - Kumngern, Montree; Knobnob, Boonying (My University, 2018)
In this paper, a new current-mode quadrature oscillator and universal filter employing two z-copy current controlled current follower transconductance amplifiers (ZC-CCFTAs) and two grounded capacitors is presented. Either a quadrature oscillator or a universal filter can be obtained into single topology. In case the circuit works as a quadrature oscillator, the condition of oscillation and the frequency of oscillation can be orthogonally controlled. In case the circuit works as a universal filter, low-pass, high-pass, band-pass, band-stop and all-pass filters can be simultaneously obtained. SPICE simulations results are presented to verify the validity of proposed circuit, which are consistent with theoretical predictions.
Keywords: analog circuit; current follower transconductance amplifier; quadrature oscillator; universal filter